RETRACTED: Curcumin Blunts IL-6 Dependent Endothelial‐to‐Mesenchymal Transition to Alleviate Renal Allograft Fibrosis Through Autophagy Activation - Zhou, Jiajun; Yao, Mengtian; Zhu, Minghui; Li, Mengchao; Ke, Qiwei; Wu, Bing; Wang, Daming (Frontiers in Immunology, 2021)
Fibrosis contributes to graft loss in chronic renal allograft injury. Endothelial‐to‐mesenchymal transition (EndMT) plays an important role in the development of fibrosis following kidney transplantation. Autophagy plays an important role in the homeostasis of diverse cell types including endothelial cells. Here we demonstrate that inhibition of autophagy by treatment with 3-methyladenine (3-MA) or by silencing autophagy-related (ATG)5 promoted interleukin (IL)-6–dependent EndMT in human umbilical vein endothelial cells (HUVECs) and human renal glomerular endothelial cells (HRGECs), and autophagy inactivation was associated with EndMT in patients with chronic allograft dysfunction. IL-6 level was significantly higher in the culture medium of HUVECs transfected with ATG5 siRNA or treated with 3-MA compared to the respective control groups. IL-6 application induced EndMT in HUVECs and HRGECs, whereas antibody-mediated neutralization of IL-6 suppressed EndMT induced by ATG5 silencing. The protective role of curcumin (Cur) against allograft fibrosis was confirmed in a rat kidney transplantation model of F344 donors to Lewis recipients. Curcumin—a natural polyphenol compound with known antifibrotic effects in various tissues—alleviated IL-6–induced EndMT and promoted autophagy in the allografted organ and in HUVECs. This is the first demonstration of the role of autophagy in renal allograft fibrosis; our findings indicate that curcumin can alleviate chronic renal allograft injury by suppressing IL-6–dependent EndMT via activation of autophagy.